The future of academic publishing - Ahmed, Abubakari; Al-Khatib, Aceil; Boum II, Yap; Debat, Humberto Julio; Gurmendi Dunkelberg, Alonso; Janicke Hinchliffe, Lisa; Jarrad, Frith; Mastroianni, Adam; Mineault, Patrick; Pennington, Charlotte R.; Pruszynski, J. Andrew (Nature Research, 2023)
Academic publishing is the backbone of science dissemination — but is the current system fit for purpose? We asked a diverse group of scientists to comment on the future of publishing. They discuss systemic issues, challenges, and opportunities, and share their vision for the future.